Differential response to dexamethasone on the TXB2 release in guinea-pig alveolar macrophages induced by zymosan and cytokines - M. E. Salgueiro; M. Conde; A. J. Seco; N. Méndez; G. Manso (Hindawi Limited, 1997)
Glucocorticosteroids reduce the production of inflammatory mediators but this effect may depend on the stimulus. We have compared the time course of the effect of dexamethasone on the thromboxane B2 (TXB2) release induced by cytokine stimulation and zymosan in guinea-pig alveolar macrophages. Interleukin-1β (IL-1β), tumour necrosis factor-α (TNF-α) and opsonized zymosan (OZ), all stimulate TXB2 release. High concentrations of dexamethasone (1-10 μM) inhibit the TXB2 production induced by both cytokines and OZ, but the time course of this response is different. Four hours of incubation with dexamethasone reduce the basal TXB2 release and that induced by IL-1β and TNF-α, but do not modify the TXB2 release induced by OZ. However, this stimulus was reduced after 24 h incubation. Our results suggest that the antiinflammatory activity of glucocorticosteroids shows some dependence on stimulus and, therefore, may have more than one mechanism involved.